AN ANALYSIS OF SYNTACTIC STRATEGIES IN THE TRANSLATION OF THE FOUNTAIN OF FAIR FORTUNE TALE - Adani Nur Sabrina (Asosiasi Dosen Muda Indonesia, 2023)
This is translation research that aims to identify the syntactic strategies implemented in the translation of The Fountain of Fair Fortune tale, as well as to analyze how the translators apply them. The syntactic strategies used are those proposed by Andrew Chesterman that fall into ten sub-categories. This qualitative research gathered the data with a purposive sampling method and analyzed the data descriptively. The result of the research shows that there are seventy-seven data found. They consist of 12 literal translations, 3 loans, 6 transpositions, 16 unit shifts, 8 phrase structure changes, 12 clause structure changes, 7 sentence structure changes, 7 cohesion changes, 1 level shift, and 4 scheme changes.